2017
DOI: 10.1080/02713683.2017.1406525
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Meibomian Gland After Exposure to Intense Pulsed Light in Meibomian Gland Dysfunction (MGD) Patients

Abstract: IPL treatment improves the symptom score of patients, associated ocular-surface indexes, MG function, and MG macrostructure as well as eyelid hygiene. And IPL treatment particularly improves MG microstructure and decreases MG inflammation in MGD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 18 publications
8
96
1
2
Order By: Relevance
“…These changes, such as MG dropout, not only have diagnostic efficacy, but also help doctors to predict the prognosis after treatment (Yin et al. ). Without doubt, the measuring method is essential in evaluating the morphologic changes, and a large number of studies have focused on this (Pult & Riede‐Pult ; Ngo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes, such as MG dropout, not only have diagnostic efficacy, but also help doctors to predict the prognosis after treatment (Yin et al. ). Without doubt, the measuring method is essential in evaluating the morphologic changes, and a large number of studies have focused on this (Pult & Riede‐Pult ; Ngo et al.…”
Section: Discussionmentioning
confidence: 99%
“…C) and vagueness might improve after effective treatment (Yin & Gong ; Yin et al. ). In other published references, MG vagueness was also mentioned as becoming less well‐demarcated (Tomlinson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments currently available are mainly palliative solutions, often insufficient to improve clinical signs and overcome patient's discomfort symptoms. Intense pulsed light was recently introduced in the field of ophthalmology and recent clinical studies showed that it is able to provide an improvement of both signs and symptoms in MGD patients (Table 2) [12][13][14][15][16][23][24][25][26][27][28][29][30][31][32][33][34][35]. IPL can be performed in combination with other therapies, like meibomian gland expression, and thus also represents a promising complementary treatment for MGD.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical safety and tolerability of IPL therapy have been confirmed by numerous clinical studies which report no major adverse events following IPL therapy [14,16,[19][20][21][22][23][24][25][26][27][28]. However, minor or transient side effects, including mild pain, light sensitivity, eyelash loss, eyelid erythema, crusting, hyperpigmentation, and blistering have been described [12,[29][30][31].…”
Section: Clinical Safetymentioning
confidence: 96%
“…The efficacy of IPL therapy has been reported by a large number of clinical studies. Retrospective and prospective nonrandomized studies have demonstrated that IPL therapy is associated with improvements in dry eye symptomology scores, tear film stability, tear osmolarity, lipid layer thickness, meibomian gland expressibility, meibum quality, eyelid margin vascularity and edema, conjunctival injection, corneal staining, and Schimer test values [12,16,[19][20][21][22][23][24][25][26][27]29,30,[34][35][36][37]. In addition, a recent prospective non-controlled study showed a reduction in tear inflammatory cytokines following IPL therapy [16], while another prospective controlled study reported significant improvement in tear protein and lipid content and composition [21].…”
Section: Clinical Efficacymentioning
confidence: 99%